Volatile Compounds and Potential Biological Activities of Essential Oil of Citrus amblycarpa Hassk. Ochse - Rasmawan, Rahmat; Marwoto, Putut; Nugroho, Sunyoto Eko (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
The utilization of volatile compounds from essential oils, one of which is citrus peels, in the food, industry, and medical fields continues to develop. This study aimed to identify volatile compounds present in the essential oils of sambal orange peels (Citrus amblycarpa Hassk. Ochse) and its potential biological activity. The research method begins with the isolation of volatile compounds via steam distillation techniques, followed by identification via gas chromatography–mass spectrometry (GC‒MS) and literature analysis related to the biological activity of the constituent compound components. The results obtained from this study revealed the dominant volatile compounds in essential oils from sambal orange peels, namely, D-limonene (37.41%), β-pinene (22.52%), germacrene D (13.21%) and α-pinene (10.79%). On the basis of the essential oil's most significant compound components, these compounds have potential as antioxidants, antibacterial agents, anti-inflammatory agents, anticancer agents, and antifungal agents. Overall, the results of this study are expected to provide direction for further research, especially for testing the biological activity of the essential oil of sambal orange peel (Citrus amblycarpa Hassk. Ochse) experimentally.